Extended family of DC-DC Quasi-Z-Source converters - Muhammad Ado; Awang Jusoh; Tole Sutikno (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The family of DC-DC q-ZSCs is extended from two to three classes and four to six members. All the members were analyzed based on efficient duty ratio range (RDeff) and general duty ratio range (RDgen). Findings showed that similar to the traditional buck-boost converter (BBC), each of the topologies is theoretically capable of inverted buck-boost (BB) operation for the RDgen with additional advantages but differed according to class in how the gains are achieved. The new topologies have advantages of BB capability at the RDeff, continuous and operable duty ratio range with unity gain at  contrary to existing topologies where undefined or zero gain is produced. Potential applications of each class were discussed with suitable topologies for applications such as fuel cells, photovoltaic, uninterruptible power supply (UPS), hybrid energy storage and load levelling systems identified.